2015
DOI: 10.3389/fpsyg.2015.01446
|View full text |Cite
|
Sign up to set email alerts
|

Early literacy experiences constrain L1 and L2 reading procedures

Abstract: Computational models of reading posit that there are two pathways to word recognition, using sublexical phonology or morphological/orthographic information. They further theorize that everyone uses both pathways to some extent, but the division of labor between the pathways can vary. This review argues that the first language one was taught to read, and the instructional method by which one was taught, can have profound and long-lasting effects on how one reads, not only in one’s first language, but also in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…For example, the idea that an atypical orientation forces a more analytical approach in word identification is supported by the emergence of a word length effect for rotated words [6,7], but not upright words. The reasoning is that if a typical left to right decoding is disrupted due to atypical orientation of a word (Coltheart et al, 2001), an analytical approach becomes necessary (i.e., relying more on sub-word units) and longer words should take more time to decode than shorter words [8]. This approach of disrupting the typical presentation has recently been used to measure holistic coding in visual word processing [9,10] and uncover cross-linguistic biases in orthographic coding [11][12][13].…”
Section: Holistic Versus Analytic Orthographic Codingmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the idea that an atypical orientation forces a more analytical approach in word identification is supported by the emergence of a word length effect for rotated words [6,7], but not upright words. The reasoning is that if a typical left to right decoding is disrupted due to atypical orientation of a word (Coltheart et al, 2001), an analytical approach becomes necessary (i.e., relying more on sub-word units) and longer words should take more time to decode than shorter words [8]. This approach of disrupting the typical presentation has recently been used to measure holistic coding in visual word processing [9,10] and uncover cross-linguistic biases in orthographic coding [11][12][13].…”
Section: Holistic Versus Analytic Orthographic Codingmentioning
confidence: 99%
“…In all three of these studies, Chinese-English bilinguals exhibited greater holistic orthographic coding and a bias towards lexical-level processing to support word identification, while Korean-English bilinguals exhibited greater analytic orthographic coding and a bias towards sublexical and phonological processing to support word identification. For example, Ben-Yehudah and colleagues (2018) found that Chinese-English bilinguals' naming times were more sensitive to word inversion and lexical frequency, whereas Korean-English bilinguals were relatively unaffected by word inversion and more sensitive to spelling-to-sound consistency [8]. Thus, prior cross-linguistic research provides evidence that individuals can exhibit differing biases for holistic versus analytic orthographic coding of English, and this differing bias is associated with a preference for lexical versus sublexical reading procedures.…”
Section: Implications Of Orthographic Coding Procedures For Word Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Inversement ceux dont la langue est opaque (e.g., français, anglais) utilisent préférentiellement des représentations plus larges telles que les unités morphémiques et les représentations lexicales globales (Sprenger-Charolles et al 1998). Ces stratégies de lecture semblent s'installer dès le début de l'apprentissage de la lecture, être durablement prépondérantes, et se transmettre à l'apprentissage de la lecture en L2 (Bhide, 2015;Ehri, 2005). Ainsi les apprenants germanophones de FLE vont vraisemblablement chercher à établir une correspondance PG univoque alors même que cette relation ne l'est pas en français.…”
Section: Interférences Des Systèmes De Cgp Français-allemandunclassified